Studi Terhadap Peran dan Strategi Layanan Perpustakaan Perguruan Tinggi Swasta di Pekanbaru Pada Masa Pandemi COVID-19 - Ajir; Yurnalis; Aryen Wildani (Perpustakaan Universitas Riau, 2022)
The purpose of this research was to determine the role of libraries and the strategy of private university library services in Pekanbaru City during the COVID-19 pandemic. This study used a qualitative description method, the sample in this study consisted of four private universities in Pekanbaru City. Data were collected through literature studies and interviews with informants. The results of the study indicate that the Pekanbaru City private university library has a role as a provider of learning resources in supporting online learning, and as a means of helping library promotions, as well as a forum for socializing the prevention of COVID-19 transmission. Then, the achievements of implementing seven categories of university library service strategies, respectively, from the highest to the lowest, namely the Riau Caltex Polytechnic Library, the STIMIK AMIK Riau Library, the Hang Tuah STIKES Library in Pekanbaru, and the Abdurrab University Library. The conclusions of this study indicate that the private university library of Pekanbaru City during the COVID-19 pandemic has a strategic role and service that can be developed holistically for the existence of the library.